2009
DOI: 10.1038/sj.bjc.6605081
|View full text |Cite
|
Sign up to set email alerts
|

C-reactive protein haplotype is associated with high PSA as a marker of metastatic prostate cancer but not with overall cancer risk

Abstract: Growing evidence points to a role for inflammation in prostate carcinogenesis. The significance of C-reactive protein (CRP), an inflammatory and innate immunity molecule, has not been evaluated thoroughly in prostate cancer (PC). In this study of 739 Finnish patients with PC and 760 healthy men, we evaluated the associations of CRP genotypes and haplotypes with total PC risk and PC progression, using prostate-specific antigen (PSA) as a marker of metastatic disease. Although the haplotype frequencies were simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
1
10
0
Order By: Relevance
“…Similar to previous studies, PSA [36,37] was associated with CRP levels in our study. While CRP may not affect by itself arterial stiffness, [38,39] it is a marker of inflammation, which has been shown to affect unfavorably arterial stiffness [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies, PSA [36,37] was associated with CRP levels in our study. While CRP may not affect by itself arterial stiffness, [38,39] it is a marker of inflammation, which has been shown to affect unfavorably arterial stiffness [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…Metabolic disorders such as diabetes are also linked to increased risk of prostate cancer (Grossmann and Wittert, 2012). Higher C-reactive protein levels are also related to increased PSA and prostate cancer, further supporting the role of chronic inflammation in prostate cancer etiology (Eklund et al, 2009). The GG genotype has also been correlated with a higher level of IL-6 among patients with chronic obstructive pulmonary disease but not among control subjects.…”
Section: Discussionmentioning
confidence: 80%
“…Another study in Finnish population confirmed the association between prostate‐specific antigen (PSA) and CRP rs1800947 variant in prostate cancer (PC). CRP alleles previously found to protect against increased CRP levels were suggested to be associated with metastatic PC, indicated by elevated PSA (Eklund et al. , 2009).…”
Section: Resultsmentioning
confidence: 99%